2011
DOI: 10.1021/bm200155t
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Copolymer Micelles Based on the Complementary Multiple Hydrogen Bonds of Nucleobases for Drug Delivery

Abstract: Novel supramolecular copolymer micelles with stimuli-responsive abilities were successfully prepared through the complementary multiple hydrogen bonds of nucleobases and then applied for rapid intracellular release of drugs. First, both adenine-terminated poly(ε-caprolactone) (PCL-A) and uracil-terminated poly(ethylene glycol) (PEG-U) were synthesized. The supramolecular amphiphilic block copolymers (PCL-A:U-PEG) were formed based on multiple hydrogen bonding interactions between PCL-A and PEG-U. The micelles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 49 publications
2
105
0
Order By: Relevance
“…225-300 nm) for PVBT/PVBA = 30/70, 50/50 and 70/30. In addition, multiple complementary hydrogen bonds are sensitive to the variation of environments, such as temperature and solvents, which will be discussed in our further study [52][53][54]. …”
Section: Multiple Hydrogen Bonding Interactions In Pvbt/pvba Blend Comentioning
confidence: 99%
“…225-300 nm) for PVBT/PVBA = 30/70, 50/50 and 70/30. In addition, multiple complementary hydrogen bonds are sensitive to the variation of environments, such as temperature and solvents, which will be discussed in our further study [52][53][54]. …”
Section: Multiple Hydrogen Bonding Interactions In Pvbt/pvba Blend Comentioning
confidence: 99%
“…This property was employed for the encapsulation of chemicals using polymeric drug carriers, 3 as well as for the synthesis of membranes, 4 for instance. Many routes led the synthesis of amphiphilic copolymers using sequential polymerization of CROP and CRP 5 and especially CROP and RITP.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with observations that the triggering mechanisms for most particulate carriers occur in the endosome and release the drugs into the cytoplasm. 43 The red and green fluorescence were not overlay completely, which indicated that some DOX was successfully released inside the cells from the polymeric micelles (Fig. 7, Line 4).…”
Section: Drug Release From Micellesmentioning
confidence: 99%